Impact of PLAI conferences, etc. to the professional development of librarians and information professionals, 1991-1995 - Villanueva, Aloha O.; Cruz, Ma. Divina P.; Santos, Herminia H. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1997)
This study was conducted to find out if conferences, seminar-workshops, lecture-forums and other activities sponsored by the PLAI (Philippine Librarians Association, Inc.) from 1991 had any impact on the professional development of its members.
A Likert-type questionnaire was administered to 200 librarians and information professionals from all over the country who were members of the PLAI from 1991 to 1995. Out of 85 accomplished questionnaires returned, only 72 were considered. Eight were disregarded due to non-attendance at any six conferences and five due to inconsistent answers. Percentages, modes, and means were used to analyze the data received.
The findings of the study that the respondents perceived PLAI-sponsored conferences from 1991 to 1995 have met the objectives of the conferences, etc. These conferences helped a lot in increasing the knowledge of librarians and information professionals in their work. The findings also revealed that PLAI-sponsored conferences were relevant to their work and have positive effects on their job performance.
Computer print-out.
Vita.
Special Problem (Master of Library Science)
Keywords: Philippine Librarians Association, Inc; Library science -- Philippines -- Societies, etc; Congresses and conventions -- Philippines; Library education (Continuing education) -- Philippines; Professional associations -- Philippines; Library associations -- Philippines; Library science -- Philippines -- Congresses